2020
DOI: 10.21203/rs.3.rs-42831/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Methods and Effectiveness of Communication Between Hospital Allied Health and Primary Care Practitioners: a Systematic Narrative Review

Abstract: Background There is a compelling rationale that effective communication between hospital allied health professionals and primary care practitioners could improve quality and continuity of patient care. It is not known which methods of communication are used, nor how effectively they facilitate the transition of care when a patient is discharged home from hospital. Our systematic review aims to investigate the methods and effectiveness of communication between hospital allied health professionals and primary ca… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
(116 reference statements)
0
1
0
Order By: Relevance
“…In terms of specific collaboration content, Lemetti [9] revealed the importance of collaboration between the hospital and primary health care providers for continuity of care for elderly patients. Sheehan [10] found that communication and coordination between hospitals and primary care institutions can ensure comprehensive people-oriented care. Otte [11] points out that available evidence shows that effective collaboration between general practitioners and hospital doctors can lead to measurable health benefits, better use of resources, improved patient experience, and improved health outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of specific collaboration content, Lemetti [9] revealed the importance of collaboration between the hospital and primary health care providers for continuity of care for elderly patients. Sheehan [10] found that communication and coordination between hospitals and primary care institutions can ensure comprehensive people-oriented care. Otte [11] points out that available evidence shows that effective collaboration between general practitioners and hospital doctors can lead to measurable health benefits, better use of resources, improved patient experience, and improved health outcomes.…”
Section: Introductionmentioning
confidence: 99%